Housing in the US : current issues - Karianov, Roman (2024)
The United States is currently experiencing an affordable housing crisis. This paper examines the role of housing in the economy and provides a detailed view of the U.S. residential real estate market. The analysis indicates that the primary reasons for the shortage of homes include insufficient construction, a lack of public housing programs, community resistance, and legal restrictions. This paper also provides an overview of the U.S. mortgage lending system and focuses on current problems in this sector. A notable rise in house prices requires greater reliance on borrowing and rapid changes in interest rates have led to problems such as the rate lock-in effect and rising delinquency rates. The regulatory burden reduces the competitiveness of banks in the mortgage market, which eventually leads to a shift of credit risk to government-sponsored enterprises. The last part of the paper attempts to identify predictors of mortgage delinquencies. The Granger causality test indicates that the real GDP growth and the effective Fed funds rate may be useful in predicting the delinquency rate on single-family residential mortgages.